Future City Glasgow: programs of action, tensions and contradictions of a smart city project (Comunicação & Inovação, 2016)
This paper analyses economic factors related to the public space surveillance apparatus in the project Future City Glasgow, a model for official standards for smart cities in the United Kingdom. The study was carried out by an international network of researchers gathered around the project "Augmented urbanity and smart technologies: how 'smart' are our cities becoming?", funded by the Newton Fund. The article relies on the Actor network Theory, on a Brazilian model for the classification of smart cities projects, and on the Infralab methodology, under development by the aforementioned research network.
Keywords: Smart city. Surveillance. Actornetwork Theory.